Congenital Muscular Dystrophies and Cognitive Impairment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Reserchers at the Department of Paediatric Neurology, Catholic University, Rome and other Italian centers specializing in neuromuscular disease studied the prevalence of congenital muscular dystrophy (CMD) in the Italian population, and the frequency of individual genetically defined forms, including de novo phenotypes.